Sodium ion battery negative electrode material and preparation method thereof

By using a combination of 85% hard carbon particles, 8% conductive carbon black, 2% styrene butadiene rubber, 2% sodium carboxymethylcellulose and 3% binder in the sodium ion battery negative electrode material, combined with a specific preparation method, The problem of the pore size and layer spacing of the sodium ion battery negative electrode material are solved, the discharge capacity and cycle stability are improved, the performance optimization of the sodium ion battery negative electrode material is achieved, and fast charging and breadth applications are supported.

CN119170741AInactive Publication Date: 2024-12-20SHENZHEN MELASTA BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411642379.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The pore diameter and layer spacing of graphite in the existing sodium ion battery negative electrode materials are small, which does not match the sodium ion diameter, which cannot meet the requirements of sodium ion battery negative electrodes, and the sodium storage capacity of soft carbon materials is insufficient.

Method used

Using sodium ion battery negative electrode material consisting of 85% hard carbon particles, 8% conductive carbon black, 2% styrene-butadiene rubber, 2% carboxymethylcellulose sodium and 3% binder, the hard carbon particles include disorderly distributed Graphite-like layer sheets, the pore size and layer spacing of the material are improved by specific preparation methods, including 85% hard carbon particles, 8% conductive carbon black, 2% styrene butadiene rubber, 2% carboxymethylcellulose sodium and 3% adhesive The tap density and particle size range of the hard carbon particles are 0.8-2.2 g/cm3 and 2 μm to 50 μm, the carbon layer spacing of the graphite-like layer sheet is 0.3363 nm to 0.3357 nm, and the average pore size of the hard carbon particles is 0.5 nm. ~5nm, the ash size range is 0.10% to 0.35%, the specific surface area is 0.7 m2/g ~2.5 m2/g, the adhesive contains polyacrylic acid derivatives, and is prepared by biomass carbon sources such as coconut shells, straws, etc.

Benefits of technology

Improve the discharge specific capacity of hard carbon negative electrode material, has high charge and discharge rate, safe and reliable, and excellent low-temperature performance, solves the safety problem of overdischarge, improves cycle life and capacity, and realizes the performance optimization of the negative electrode material of sodium ion battery , supports fast charging and breadth applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170741A_ABST
    Figure CN119170741A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery negative electrode material and a preparation method thereof, the negative electrode material comprises, by mass, 85% of hard carbon particles, 8% of conductive carbon black, 2% of styrene butadiene rubber, 2% of sodium carboxymethyl cellulose and 3% of a binder, the hard carbon particles comprise disorderly distributed graphite-like layer sheets, the tap density range of the hard carbon particles is 0.8-2.2 g / cm < 3 >, and the thickness of the conductive carbon black is 0.5-1.5 mm. The particle size of the hard carbon particles ranges from 2 microns to 50 microns, the carbon interlayer spacing d002 value of the graphite-like lamellas ranges from 0.3363 nm to 0.3357 nm, the average pore size of the hard carbon particles ranges from 0.5 nm to 5 nm, the ash content ranges from 0.10% to 0.35%, the specific surface area ranges from 0.7 m < 2 > / g to 2.5 m < 2 > / g, and the adhesive comprises polyacrylic acid derivatives. According to the technical scheme, a large number of closed pores can be generated in the hard carbon material, the pore structure of the hard carbon is effectively improved, embedding and deposition of sodium ions are more suitable, the conductivity and stability of the hard carbon are enhanced, the sodium-ion battery has larger charge-discharge specific capacity, the sodium storage performance of the hard carbon is improved, and the service life of the sodium-ion battery is prolonged. The sodium storage performance and the first effect of the sodium-ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery negative electrode material and a preparation method thereof. Background Art

[0002] As people's urgent demand for high-performance, low-cost battery technology becomes increasingly apparent, sodium-ion batteries are becoming increasingly popular in the market due to their significant advantages such as short charging time, high energy density, low cost and recyclability. Sodium-ion batteries are a type of secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive and negative electrodes to work. Similar to the working principle of lithium-ion batteries, during the charging and discharging process, Na+ is embedded and deintercalated between the two electrodes: during charging, Na+ is deintercalated from the positive electrode and embedded in the negative electrode through the electrolyte; during discharging, the opposite is true. Sodium-ion batteries use the transfer of sodium ions (rather than lithium ions) to store and release electrical energy.

[0003] The electrode material used in sodium-ion batteries is mainly sodium salt, which is more abundant and cheaper than lithium salt. Since sodium ions are larger than lithium ions, sodium-ion batteries are a cost-effective alternative when weight and energy density are not required. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: (1) Sodium salt raw materials are abundant and cheap. The use of iron-manganese-nickel-based positive electrode materials reduces the cost of raw materials by half compared with lithium-ion battery ternary positive electrode materials; (2) Due to the characteristics of sodium salt, low-concentration electrolytes can be used (for the same concentration of electrolyte, the conductivity of sodium salt is about 20% higher than that of lithium electrolyte) to reduce costs; (3) Sodium ions do not form alloys with aluminum, and aluminum foil can be used as the negative electrode current collector, which can further reduce costs by about 8% and weight by about 10%; (4) Due to the non-overdischarge characteristic of sodium-ion batteries, sodium-ion batteries are allowed to discharge to zero volts. The energy density of sodium-ion batteries is greater than 100Wh / kg, which is comparable to lithium iron phosphate batteries, but its cost advantage is obvious, and it is expected to replace traditional lead-acid batteries in large-scale energy storage. The application of sodium-ion battery negative electrode materials is mainly concentrated in the fields of energy storage and electric two-wheeled vehicles. In addition, sodium-ion batteries also have excellent cycle life and a wide operating temperature range, can operate in extreme environments, and are suitable for cold regions.

[0004] The negative electrode materials of sodium-ion batteries generally have a low reduction potential and play an important role in loading and releasing sodium ions: a reduction reaction occurs during charging and an oxidation reaction occurs during discharging. The efficiency of the negative electrode material directly affects the overall kinetic performance of the battery, such as rate performance, power density, etc. In recent years, research on negative electrode materials for sodium-ion batteries has made significant progress. Researchers have continuously improved the sodium storage performance and cycle stability of negative electrode materials by modifying graphite, developing new carbon-based materials, and exploring alloy reaction materials.

[0005] The existing technical routes for negative electrode materials of sodium batteries include metal oxides, organic negative electrode materials, negative electrode materials based on conversion and alloying reactions, and carbon-based negative electrode materials. Among them, metal oxides have low capacity, poor alloy cycle performance and rate performance, and graphite is difficult to store sodium, so it cannot be used as a negative electrode for sodium batteries. Compared with lithium-ion batteries, the atomic radius of sodium ions is at least 35% larger than that of lithium ions. The interlayer spacing of graphite negative electrodes is only 0.3354 nanometers. It is difficult for sodium ions to embed and detach from the material, which puts higher requirements on the structural stability of negative electrode materials. The pore size and interlayer spacing of the mainstream graphite negative electrode materials used in lithium-ion batteries cannot meet the requirements of sodium-ion battery negative electrodes. Although soft carbon has a lower cost than hard carbon, it has a lower sodium storage capacity due to its graphitized structure; although the capacity can be increased through the pore-making process, it will increase the cost and is not as economical as hard carbon. Summary of the invention

[0006] The main purpose of the present invention is to propose a sodium ion battery negative electrode material and a preparation method thereof, aiming to solve the technical problems that the pore size and interlayer spacing of graphite in the existing sodium battery negative electrode materials are small, which are inconsistent with the diameter of sodium ions and cannot meet the requirements of the sodium ion battery negative electrode, and the soft carbon material has insufficient sodium storage capacity due to its graphite-like structure.

[0007] To achieve the above object, the sodium ion battery negative electrode material proposed in the present invention comprises, by mass percentage, 85% of hard carbon particles, 8% of conductive carbon black, 2% of styrene-butadiene rubber, 2% of sodium carboxymethyl cellulose and 3% of a binder, wherein the hard carbon comprises disorderly distributed graphite-like layers, and the tap density of the hard carbon particles is in the range of 0.8-2.2 g / cm 3 The particle size of the hard carbon particles ranges from 2 μm to 50 μm, the carbon interlayer spacing d002 value of the graphite-like layers ranges from 0.3363 nm to 0.3357 nm, the average pore size of the hard carbon particles ranges from 0.5 nm to 5 nm, the ash content ranges from 0.10% to 0.35%, and the specific surface area ranges from 0.7 m 2 / g ~2.5m 2 / g, the adhesive comprises a polyacrylic acid derivative.

[0008] Optionally, the raw material of the hard carbon particles is a biomass carbon source, and the biomass is one or more of coconut shells, straws, peanut shells, corn stalks, bamboo, glucose, starch and lignin.

[0009] On the other hand, the present invention also provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps: Step 1: Raw material screening and pretreatment: one or more of coconut shells, straw, peanut shells, corn stalks and bamboo are selected as biomass carbon source raw materials, and the biomass carbon source raw materials are cleaned to remove impurities, dried in a dryer, and then crushed in a grinder; Step 2: pre-carbonization: the biomass carbon source raw material crushed in step 1 is put into a protective atmosphere reactor and pre-carbonized at a temperature of 400° C. to 700° C. to obtain a pre-carbonized mixture; Step 3, pickling, pouring the pre-carbonized mixture obtained in step 2 into a reactor, adding a pore-forming agent and an acidic activator, mixing evenly, pickling, and then washing with water until neutral to obtain a precursor; Step 4: Heat up and pyrolyze. Add silicon powder and a drag reducing agent to the precursor obtained in step 3, and place it in a protective atmosphere reactor for low-temperature pre-oxidation. Then, heat it at a high temperature of 1000°C to 1300°C in an inert gas atmosphere for carbonization reaction. Step 5, ball milling, putting the mixture after the high-temperature carbonization reaction obtained in step 4 into a ball mill, adding an organic scandium grinding aid, and grinding, the ground hard carbon particles enter a magnetic separation device to remove possible residual metal impurities, and sieve according to the required particle size to obtain a porous biomass hard carbon negative electrode material; Step 6: Packaging and warehousing: Inspect the finished biomass hard carbon negative electrode material products, and package and store them after passing the inspection.

[0010] Optionally, in step three, the acidic activator is one or more of nitric acid, hydrochloric acid and hydrofluoric acid.

[0011] Optionally, in step three, the temperature in the reactor is controlled between 35°C and 45°C.

[0012] Optionally, in step three, the solid-liquid ratio in the reactor is between 1:3 and 2:1.

[0013] Optionally, in step 4, the heating time for carbonization is 2h~6h.

[0014] Optionally, in step five, the rotation speed of the ball mill ranges from 100 rpm to 300 rpm.

[0015] Optionally, in step five, the ball mill uses a ball milling diameter of 5 mm to 8 mm.

[0016] Optionally, in step 4, the inert gas is hydrogen.

[0017] The technical solution of the present invention has the following beneficial effects: the technical solution of the present invention improves the discharge specific capacity of the hard carbon negative electrode material by introducing more defects and sodium ion reaction active sites. The hard carbon material has a high charge and discharge rate, high safety and reliability, and excellent low-temperature performance, and has greatly improved capacity and cycle life. The hard carbon negative electrode material has the advantages of many sodium storage active sites, high specific capacity, small volume expansion after sodium insertion, good safety, and stable structure. It also has the characteristics of low operating voltage, high specific capacity, stable structure (small volume deformation), high first-week coulomb efficiency, high compaction density, high electronic and ion conductivity, air stability, low cost, safety and non-toxicity. The present invention can achieve performance optimization of hard carbon negative electrode materials for sodium ion batteries. The hard carbon material enables the negative electrode to better achieve fast charging, solves the safety problem of over-discharge, and opens up the breadth of application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0019] Figure 1 This is a process step diagram of a method for preparing a negative electrode material for a sodium ion battery according to an embodiment of the present invention.

[0020] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be noted that all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of the present invention are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0023] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0024] The invention provides a sodium ion battery negative electrode material and a preparation method thereof.

[0025] In one embodiment of the present invention, the negative electrode material of the sodium ion battery contains, by mass percentage, 85% of hard carbon particles, 8% of conductive carbon black, 2% of styrene-butadiene rubber, 2% of sodium carboxymethyl cellulose and 3% of a binder, the hard carbon includes disorderly distributed graphite-like layers, and the tap density of the hard carbon particles is in the range of 0.8-2.2 g / cm 3 The particle size of hard carbon particles ranges from 2μm to 50μm, the carbon interlayer spacing d002 value of graphite-like layers ranges from 0.3363nm to 0.3357nm, the average pore size of hard carbon particles ranges from 0.5nm to 5nm, the ash content ranges from 0.10% to 0.35%, and the specific surface area ranges from 0.7m 2 / g ~2.5m 2 / g, the adhesive contains polyacrylic acid derivatives.

[0026] Specifically, the raw material of the hard carbon particles is a biomass carbon source, and the biomass is one or more of coconut shells, straws, peanut shells, corn stalks, bamboo, glucose, starch and lignin.

[0027] On the other hand, Figure 1 As shown, the present invention also provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps: Step 1: Raw material screening and pretreatment: one or more of coconut shells, straw, peanut shells, corn stalks and bamboo are selected as biomass carbon source raw materials, and the biomass carbon source raw materials are cleaned to remove impurities, dried in a dryer, and then crushed in a grinder; Step 2: pre-carbonization: the biomass carbon source raw material crushed in step 1 is put into a protective atmosphere reactor and pre-carbonized at a temperature of 400° C. to 700° C. to obtain a pre-carbonized mixture; Step 3, pickling, pouring the pre-carbonized mixture obtained in step 2 into a reactor, adding a pore-forming agent and an acidic activator, mixing evenly, pickling, and then washing with water until neutral to obtain a precursor; Step 4: heating and pyrolysis, adding silicon powder and a drag reducing agent to the precursor obtained in step 3, and entering a protective atmosphere reactor for low-temperature pre-oxidation, and then heating at a high temperature of 1000°C to 1300°C in an inert gas atmosphere for carbonization reaction, and regulating its microstructure by high-temperature carbonization; Step 5, ball milling, putting the mixture after the high-temperature carbonization reaction obtained in step 4 into a ball mill, and adding an organic scandium grinding aid for grinding, the ground hard carbon particles enter a magnetic separation device to remove possible residual metal impurities, and screen according to the required particle size to obtain a porous biomass hard carbon negative electrode material. This structure helps the material to fully contact with the electrolyte, provides channels and more lithium insertion sites for the transmission of Li+ inside the material, and exhibits excellent rate and cycle performance. The presence of micropores makes the material have a large number of defect sites, which provides active sites for the storage of lithium ions and improves the lithium storage capacity. The presence of mesopores and macropores shortens the transport distance of lithium ions and improves the migration rate of lithium ions. The rich pore structure of the material helps to improve the lithium insertion capacity and cycle stability of the material; Step 6: Packaging and warehousing: Inspect the finished biomass hard carbon negative electrode material products, and package and store them after passing the inspection.

[0028] Specifically, in step three, the acidic activator is one or more of nitric acid, hydrochloric acid and hydrofluoric acid.

[0029] Specifically, in step three, the temperature in the reactor is controlled between 35°C and 45°C.

[0030] Specifically, in step three, the solid-liquid ratio in the reactor is between 1:3 and 2:1.

[0031] Specifically, in step 4, the heating time for carbonization is 2h~6h.

[0032] Specifically, in step five, the rotation speed of the ball mill ranges from 100 rpm to 300 rpm.

[0033] Specifically, in step five, the ball mill uses a ball milling diameter of 5 mm to 8 mm.

[0034] Specifically, in step 4, the inert gas is hydrogen.

[0035] Specifically, compared with lithium-ion batteries, sodium-ion batteries can achieve fast charging for three reasons: a. The Stokes diameter of sodium ions is smaller than that of lithium ions. The electrolyte of the same concentration has a higher ionic conductivity than the lithium salt electrolyte, which means that under the same conditions, sodium ions run faster than lithium ions. b. Sodium dendrites can self-dissolve, which is safer and can adapt to high-rate fast charging. According to "Exploration of the Path to Promote the Industrialization of Sodium-Ion Batteries in my country" by Ma Lin et al., since sodium metal is more active than lithium metal, the chemical stability of sodium dendrites is worse than that of lithium dendrites. Therefore, under certain conditions, they can self-dissolve in the electrolyte, solving the problem that fast charging will cause sodium dendrites to precipitate and affect battery safety. c. The larger interlayer spacing and pore size of the hard carbon negative electrode ensure that sodium ions are quickly embedded during fast charging. (2) In terms of over-discharge, sodium-ion batteries are safer than lithium-ion batteries. During over-discharge, lithium-ion batteries will cause excessive lithium removal from the negative electrode, destroying the SEI film, thereby generating CO or CO2 gas, causing the battery to swell and become dangerous. In addition, when charging after over-discharge, dead lithium will be generated at the negative electrode, reducing the battery capacity. However, sodium-ion batteries have over-discharge safety, and even discharging to 0V has little effect on the long-cycle stability of the battery cell.

[0036] Specifically, the technical solution of the present invention improves the discharge specific capacity of the hard carbon negative electrode material by introducing more defects and sodium ion reaction active sites. The hard carbon material has a high charge and discharge rate, high safety and reliability, and excellent low-temperature performance, and has greatly improved capacity and cycle life. The hard carbon negative electrode material has the advantages of many sodium storage active sites, high specific capacity, small volume expansion after sodium insertion, good safety, and stable structure. It also has the characteristics of low operating voltage, high specific capacity, stable structure (small volume deformation), high first-week coulomb efficiency, high compaction density, high electronic and ion conductivity, air stability, low cost, safety and non-toxicity. The present invention can achieve performance optimization of hard carbon negative electrode materials for sodium ion batteries. The hard carbon material enables the negative electrode to better achieve fast charging, solves the safety problem of over-discharge, and opens up the breadth of application of sodium ion batteries.

[0037] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A sodium ion battery negative electrode material, It is characterized in that The negative electrode material contains 85% hard carbon particles, 8% conductive carbon black, 2% styrene-butadiene rubber, 2% sodium carboxymethyl cellulose and 3% binder by mass percentage, the hard carbon includes disorderly distributed graphite-like layers, and the tap density of the hard carbon particles is in the range of 0.8-2.2 g / cm 3 The particle size of the hard carbon particles ranges from 2 μm to 50 μm, the carbon interlayer spacing d002 value of the graphite-like layers ranges from 0.3363 nm to 0.3357 nm, the average pore size of the hard carbon particles ranges from 0.5 nm to 5 nm, the ash content ranges from 0.10% to 0.35%, and the specific surface area ranges from 0.7 m 2 / g ~2.5m 2 / g.

2. The sodium ion battery negative electrode material according to claim 1, It is characterized in that The raw material of the hard carbon particles is a biomass carbon source, and the biomass is one or more of coconut shells, straws, peanut shells, corn stalks, bamboo, glucose, starch and lignin.

3. A method for preparing a negative electrode material for a sodium ion battery, for preparing the negative electrode material for a sodium ion battery as claimed in any one of claims 1 to 2, It is characterized in that The following steps are involved: Step 1: Raw material screening and pretreatment: one or more of coconut shells, straw, peanut shells, corn stalks and bamboo are selected as biomass carbon source raw materials, and the biomass carbon source raw materials are cleaned to remove impurities, dried in a dryer, and then crushed in a grinder; Step 2: pre-carbonization: the biomass carbon source raw material crushed in step 1 is put into a protective atmosphere reactor and pre-carbonized at a temperature of 400° C. to 700° C. to obtain a pre-carbonized mixture; Step 3, pickling, pouring the pre-carbonized mixture obtained in step 2 into a reactor, adding a pore-forming agent and an acidic activator, mixing evenly, pickling, and then washing with water until neutral to obtain a precursor; Step 4: Heat up and pyrolyze. Add silicon powder and a drag reducing agent to the precursor obtained in step 3, and place it in a protective atmosphere reactor for low-temperature pre-oxidation. Then, heat it at a high temperature of 1000°C to 1300°C in an inert gas atmosphere for carbonization reaction. Step 5, ball milling, putting the mixture after the high-temperature carbonization reaction obtained in step 4 into a ball mill, adding an organic scandium grinding aid, and grinding, the ground hard carbon particles enter a magnetic separation device to remove possible residual metal impurities, and sieve according to the required particle size to obtain a porous biomass hard carbon negative electrode material; Step 6: Packaging and warehousing: Inspect the finished biomass hard carbon negative electrode material products, and package and store them after passing the inspection.

4. The method for preparing the negative electrode material for a sodium ion battery according to claim 3, It is characterized in that In the step three, the acidic activator is one or more of nitric acid, hydrochloric acid and hydrofluoric acid.

5. The method for preparing the negative electrode material for sodium ion batteries according to claim 3, It is characterized in that In the step 3, the temperature in the reactor is controlled between 35°C and 45°C.

6. The method for preparing the negative electrode material for sodium ion batteries according to claim 3, It is characterized in that In the step 3, the solid-liquid ratio in the reactor is between 1:3 and 2:

1.

7. The method for preparing the negative electrode material for a sodium ion battery according to claim 3, It is characterized in that In the step 4, the heating time for carbonization is 2h~6h.

8. The method for preparing the negative electrode material for sodium ion batteries according to claim 3, It is characterized in that In the step 5, the rotation speed of the ball mill ranges from 100 rpm to 300 rpm.

9. The method for preparing the negative electrode material for a sodium ion battery according to claim 3, It is characterized in that In the step 5, the ball mill uses a ball milling diameter of 5 mm to 8 mm.

10. The method for preparing the negative electrode material for sodium ion battery according to claim 3, It is characterized in that In the step 4, the inert gas is hydrogen.

Citation Information

Patent Citations

  • Preparation method of high-capacity biomass hard carbon negative electrode material for sodium ion battery

    CN116374993A

  • Hard carbon negative electrode material, preparation method and sodium ion battery

    CN116646519A

  • Hard carbon material and preparation method thereof, negative electrode material and sodium ion battery

    CN117594794A

  • Palm fruit shell derived hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN117623276A

  • Hard carbon material, negative electrode plate, and electrochemical device

    US20240322172A1